Oral and extraoral manifestationse of sturge-Weber syndrome: A rare finding - Amitandra K Tripathi; Mohammad Arif Khan; Krishna Deo; Ranjan Mani Tripathi (Wolters Kluwer Medknow Publications, 2016)
Sturge-Weber syndrome (SWS) is a rare congenital developmental disorder characterized by unilateral cutaneous vascular malformation (nevus flammeus or port-wine stains) in association with ipsilateral leptomeningeal angiomatosis and glaucoma. This article presents a case of SWS associated with gingival hyperplasia and pyogenic granuloma.